Effects of Gelatin-Saccharides Interactions on the Physicochemical Properties and in Vitro Digestion of Cold-set Gels - Xinyu ZHAI; Xiaorui XING; Ruican WANG; Pixian ZHANG; Shuo WANG (Shipin gongye ke-ji)
This study aimed to clarify the effects of physico-chemical interactions between gelatin and different saccharides (including allulose, fructose, fructo-oligosaccharides (FOS), and sucrose) on the properties (hardness, color, in-vitro digestibility, etc.) of gelatin-saccharide mixed gels. Gelatin was mixed with the various concentrations of saccharides at a high temperature and then cooled to prepare cold-set gels, with the texture and color of gels characterized using a texture analyzer and a colorimeter. Based on evident browning of the gels, the Maillard reaction-induced changes in reducing sugar and free amine contents as well as the UV-visible light absorption of Maillard reaction products in each gel were characterized. In addition, the gels’ protein molecular weight distribution, in-vitro protein digestibility, and the antioxidant properties of digesta were compared through SDS-PAGE, in-vitro digestion, and antioxidant assays. The results indicated that in terms of texture, gels with allulose and fructose were softer, with hardness ranging from 10.5 to 12.6 N, while those with sucrose and FOS were harder, with the highest hardness being 29.9 N and 22.2 N respectively. Except for sucrose (a non-reducing sugar), the Maillard reaction occurred to limited degrees in mixtures with 30%~50% saccharides, with a reducing sugar loss rate of less than 10%, and free amine content ranging from 3.6 to 3.8 mg/g. At 72% saccharide concentration, the maximum reducing sugar loss rate could reach 17.6%, with free amine content less than 3.2 mg/g, intensifying the Maillard reaction. Allulose exhibited higher Maillard reactivity compared to fructose, whereas FOS, containing about 50% reducing sugars, showed weaker reaction. Under mild thermal processing condition, the Maillard reaction caused slight crosslinking of gelatin subunits but did not significantly affect the in-vitro digestibility of protein, with an in vitro digestibility rate between 23% and 25%, but significantly increased the ABTS+ and DPPH free radical scavenging rates of the gel digesta (P<0.05).